Psychological and behavioral profile of sexual abusers of children (Archives of Clinical Psychiatry, 2009)
BACKGROUND: Sexual violence against children is a universal problem, occurring since ever, everywhere and regardless the socio-economic status. Whist most studies have been dedicated to the victim of such crime, there is little information regarding their perpetrators, which is largely limited to the description of demographic data. OBJECTIVE: Review the literature regarding children sexual aggressors according to psychological and behavioral profile. METHODS: Literature review and discussion. RESULTS: Presentation of the major classifications of offenders, pointing out the most widely used ones and the implications to forensic psychiatry and psychology. CONCLUSION: The psychological and behavioral profile use is very important for medico-legal practice, but still needs better scientific validation.